2003
DOI: 10.1148/radiol.2261011827
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Depiction of Hepatocellular Carcinoma: Ferumoxides-enhanced MR Imaging versus Triple-Phase Helical CT

Abstract: Ferumoxides-enhanced MR imaging is superior to triple-phase helical CT for the preoperative depiction of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 31 publications
2
44
0
2
Order By: Relevance
“…Upon review of the image, the observers were aware that sensitivity was calculated with the number of lesions assigned a confidence level of 3 or 4. In clinical practice at our institution, nodules that became enhanced in the arterial phase and had a washout pattern in the portal or equilibrium phase with or without capsular enhancement at triple-phase MDCT were considered HCC [4,[16][17][18][19]. The criteria for HCC on gadoxetic acid-enhanced MR images were similar to the criteria for the triple-phase dynamic CT pattern: enhancement in the arterial phase and a washout pattern in the portal or 3-min late phase that revealed the mixed enhancing features of both equilibrium phase and hepatobiliary phase images as hepatocyte-related enhancement starts approximately 1 min after intravenous injection of gadoxetate disodium [20].…”
Section: Image Analysismentioning
confidence: 99%
“…Upon review of the image, the observers were aware that sensitivity was calculated with the number of lesions assigned a confidence level of 3 or 4. In clinical practice at our institution, nodules that became enhanced in the arterial phase and had a washout pattern in the portal or equilibrium phase with or without capsular enhancement at triple-phase MDCT were considered HCC [4,[16][17][18][19]. The criteria for HCC on gadoxetic acid-enhanced MR images were similar to the criteria for the triple-phase dynamic CT pattern: enhancement in the arterial phase and a washout pattern in the portal or 3-min late phase that revealed the mixed enhancing features of both equilibrium phase and hepatobiliary phase images as hepatocyte-related enhancement starts approximately 1 min after intravenous injection of gadoxetate disodium [20].…”
Section: Image Analysismentioning
confidence: 99%
“…Moreover, several investigators reported that ferumoxide-enhanced MRI appeared to be superior to CTAP and dual-or triplephase helical CT to detect hepatocellular carcinoma (16,22,23). In addition, Reimer et al reported that the ferucarbotran-enhanced MRI appeared to be superior to the dual-or triple-phase helical CT images for the detection of hepatic lesions (20).…”
Section: Discussionmentioning
confidence: 99%
“…First, a well-differentiated hepatocellular carcinoma may result in the active uptake of ferucarbotran particles, which results in iso-or hypointensity on ferucarbotran-enhanced images. Previous studies (16,19) have pointed out that a variety of hepatic tumors, such as focal nodular hyperplasia, regenerative nodule, hepatic adenoma, dysplastic nodule, and well-differentiated hepatocellular carcinomas can display a variable uptake of SPIO, since these tumors contain a variable number of Kupffer's cells. Therefore, it may be difficult to distinguish well-differentiated hepatocellular carcinoma from other benign hepatic tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPIO-enhanced MR imaging has been reported to be useful for the detection of both metastatic (1,2) and primary (3,4) liver tumors.…”
mentioning
confidence: 99%